Příklady z matematiky

                      (x+1)2+(y+1)2+10 = x(x+6) +y(y+6)

                         (x+1)2-(y+1)2+8 = x (x-6)- y(y-6)                           

             x2+2x+1+y2+2y+ 1+ 10 = x2+6x+y2+6y

               x2 +2x +1 -y2 -2y -1+ 8 = x2-6x-y2+6y

                           2x+1+2y+1+10 = 6x + 6y

                          2x+ 1 -2y -1+8 = -6x + 6y

                                          -4x -4y = -12 / ( 2)

                                        8x – 8y = -8

                                         -8x -8y = -24

                                         8x – 8y = -8

                                             -16y = -32

                                                      y = 2

 

x =                     = 1

 

 

L1= (1+1)2 + (2+1)2 + 10 = 23

P1 =1(1+6) + 2(2+6) = 23

 

L2 = (1+1)2-(2+1)2 +8= 3

P2 = 1(1-6) -2(2-6) = 3

 

 

                                 P = [ 1;  2 ]